Thermal Properties Investigation of FeCr Alloy Using Lammps Simulation: A Preliminary Study - Mardiyanto Mangun Panitra; Syahfandi Ahda; Abu Kahlid Rivai (BRIN, 2019)
At present, nuclear reactor technology that is widely used because of its proven reliability is the gen-III + nuclear reactor. Even if it is seen from the aspect of safety and reliability of this generation reactor, it has been proven, but because nuclear energy plays a vital role to meet the growing world energy needs, it is necessary to have a type of nuclear reactor that is tailored to those needs.The next generation of nuclear reactors must meet the requirements of fulfilling safety requirements, be flexible, a longer operating life (more than 60 years), more economical. In order for a reactor to produce higher power, a longer operating life and more economical, reactor structure materials which are capable of being operated at high temperatures are needed. The types of materials that are expected to meet these requirements include various types of ferritic / martensite steel, austenite, alloy steel containing nickel, and metal glass materials and ceramic materials. FeCr metal alloys are alloys that form the metals mentioned above, so it is important to conduct research both in simulation and experiment. Molecular Dynamics simulation of FeCr alloys using Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) has been done to explore their thermodynamic characteristics such as heat treatment, solubility of Cr, atomic radial distribution function (RDF). The results of the simulation are illustrated using Visual Molecular Dynamics (VMD) code.Â